Konsep Hotel Resort dengan Pendekatan Arsitektur Neo Vernakular di Kawasan Bromo - Ahmad yusuf Fahrezzi; Eva Elviana (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
The Mount Bromo vacation spot is a well-known tourist destination that attracts both local and foreign visitors. Many tourists come for the breathtaking natural scenery. Needless to say, accommodation and hotels are essential to provide a comfortable stay for tourists who want to explore the tourist areas of Bromo. Resort hotels offer travelers a respite from the hustle and bustle of the city. The design process uses exploratory techniques. Exploratory research is research that involves conducting research and expanding the concept of exploitation to include broader conceptual aspects of research. The hotel design layout is meant to assist authorities' efforts to enhance tourism withinside the Mount Bromo region, which includes leveraging its herbal ability in tourism. The architectural goal of this resort hotel is to build accommodations that help to harness and capitalize on the tourism potential of the Mount Bromo region. The design of the Mount Bromo Tourism Center is based on a neo-vernacular approach, which is a construction concept that incorporates modern elements and attempts to adapt to the environment. The concept encompasses significant aspects of form, functionality, and technology and blends seamlessly with the present-day setting.